The Buddhism and Psychology Discourse: A Hermeneutic - Payne, Richard K. (Journal of global buddhism, 2021)
A primary conceptual framework for Buddhism in contemporary popular religious culture is as a kind of psychology. This representation dates from the nineteenth century, when apologists took advantage of the new cultural discourse of psychology to explain Buddhism in ways that made it accessible, familiar, acceptable, and more easily incorporated into modern, religious consumerism. This essay is a hermeneutic examination of this psychologizing discourse. It describes three forms of that discourse, identified here as "interpretation of," where Buddhism is seen in psychological terms, "interpretation as," where Buddhism becomes a form of psychology, and " interpretation ," where the interpretive act is erased and Buddhism and psychology become unproblematically identical.